1. Wykonaj mnożenie i zredukuj wyrazy podobne.
a) (x-5)(x+5) + 2xy=
b) (3-a)(6-3a)+3a=
c) (-2+x)(2+x)=
d) (-4-x)(4+2x)=
e) (-2-2x)(-4+3x)=
f) (-6-3x)(-5-8x)=
2. Rozwiąż równianie.
a) 3x(x-1)= 3x²+6
b) -4x(2-x)= 2(x²+16)+2x²
c) x²-3(x+1)= -x(2-x)
d) x²-2x= x(x-1)
e) 3x²+6= 3x(x-2)
f) (x+2)(3+x)= x(x+1)+2
g) (3a-7)a+5= a²+2a(a-1)
h) -(x-3)(2x+1)= -2(6+x²)

Liczę na szybkie rozwiązanie :>

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-14T22:03:58+01:00
A) (x-5)(x+5) + 2xy= x² - 25 + 2xy

b) (3-a)(6-3a)+3a= 18 - 9a - 6a + 3a² + 3a = -12a + 3a² + 18

c) (-2+x)(2+x)= (x-2)(x+2) = x² - 4

d) (-4-x)(4+2x)= -16 - 8x - 4x - 2x² = -12x - 2x² - 16

e) (-2-2x)(-4+3x)= 8 - 6x + 8x - 3x² = 2x - 3x² + 8

f) (-6-3x)(-5-8x)= 30 + 48x + 15x + 24x² = 63x + 24x² + 30

2. Rozwiąż równianie.
a) 3x(x-1)= 3x²+6
3x² - 3x = 3x² + 6
-3x = 6
x = -2

b) -4x(2-x)= 2(x²+16)+2x²
-8x + 4x² = 2x² + 32 + 2x²
-8x + 4x² - 4x² = 32
-8x = 32
x = -4

c) x²-3(x+1)= -x(2-x)
x² - 3x - 3 = -2x + x²
-3x + 2x = 3
-x = 3
x = -3

d) x²-2x= x(x-1)
x² - 2x = x² - x
-2x + x = 0
-x = 0
x = 0

e) 3x²+6= 3x(x-2)
3x² + 6 = 3x² - 6x
6 = -6x
x = -1

f) (x+2)(3+x)= x(x+1)+2
3x + x² + 6 + 2x = x² + x + 2
5x - x = 2 - 6
4x = - 4
x = -1

g) (3a-7)a+5= a²+2a(a-1)
3a² - 7a + 5 = a² + 2a² - 2a
-7a + 2a = -5
- 5a = -5
a = 1

h) -(x-3)(2x+1)= -2(6+x²)
-(2x² + x - 6x - 3) = -12 - 2x²
-2x² - x + 6x + 3 = -12 - 2x²
5x = -12 - 3
5x = -15
x = -3